TEKNIK PERSUASI PADA IKLAN SKIN CARE DI MEDIA SOSIAL INSTAGRAM - Johana Widya Lestari; Mimas Ardhianti (Buana Bastra, 2018)
The background of the study is seen from many advertisers who give promises about the product to the customors. In the skin care product, they mostly use instagram as a persuasion social media to engage the viewers and customors. The purpose of this study was to describe the persuasion technique on the skin care product in social media Instagram. The theory of this study used persuasion technique by Sunarjo. The data of this study were written data, there were; cognitive dissonance, pay of idea and fear arrousing, emphaty, packing, red herring, and association technique. The researcher used qualitative approach. Source of the data in this study was written source that was skin care advertisement in Instagram named Jafraskincare_bdg (Jul-November 2017) The data collection used documentation. Data analysis used qualitative descriptive technique. The result of the study on the skin care advertisement in social media Instagram included: 1) cognitive dissonance technique, 2) pay of idea and fear arousing technique, 3) emphaty technique, 4) packing technique, 5) red herring technique, 6) association technique, it also found 7) the combination between pay off idea and packing technique also the combination between pay off idea and fear arrousing technique.